Literasi Teknologi Informasi sebagai Bekal Anak Sekolah Dasar di Era Digital - Renny Permata Saputri; Monica Fransisca (CV. ITTC INDONESIA, 2025)
This Community Service (PKM) activity aims to foster information technology literacy awareness from an early age among students at SD Negeri 31 Jati Tanah Tinggi Padang. Amidst the rapid development of the digital era, the skill of using technology wisely and productively has become an urgent need for the younger generation, including elementary school-aged children. This activity was conducted using an educative and interactive approach, including an introduction to basic ICT devices, safe internet practices, and the use of age-appropriate educational applications. Through enjoyable and participatory delivery methods, it is expected that students can understand the positive benefits of technology and utilize it to support their learning process. This program also contributes to the implementation of the Tri Dharma of Higher Education, specifically in the form of community service.